Peran Faktor Nutrisi pada Pencegahan Kanker Prostat - TAMBUNAN, NICHOLAS (Indonesian Journal of Cancer, 2014)
Prostate cancer is a malignancy disease which originates in prostate organ that only can be found in men. This cancer is the second most common in men after lung cancer and the fifth in the entire world. The incidence will be increasing in the fifth decade of life with the peak in the eight decade. Several factors which are thought to be the etiology are: genetic, hormonal, diet, environment, and infection. Diet factor has great influence for both, the development and the prevention of this disease. Man who consumes high fat diet will have not only the risk to get that disease but also will increase the progresiveness of the disease. Several nutrients that are thought for decreasing the incidence of the prostate cancer are cruciferous vegetables and fruits which contain carotenoid. Furthermore, soya which contains much of isoflavon or phytoestrogen can also acts as the prevention of development of cancer cell. Green tea, lycopene ( carotenoid group that can be found in tomato products) can also act as the source of the antioxidant. This paper will discuss the role of nutrition factors of lycopene and soya in prostate cancer.